Taktik Kampung Batik Telaga dalam Pemberdayaan Ekonomi Perempuan - Rohmanur Aziz; Putri Diesy Fitriani; Syifa Fauziah (UIN Sunan Gunung Dajti Bandung, 2023)
The inequality of women's roles in carrying out their movements is one of the triggers for women's inconsistency in efforts to prosper the economy in the family because of various barriers that limit their movements. Gender grouping and patriarchy systems that encroach on women hinder women's movements in the public sphere. Due to these problems, Batik villages have become a place for empowering women to balance the role and function of women in the public sector without neglecting their role in the domestic sphere. This study aims to determine the tactics of kampung batik telaga in carrying out women's economic empowerment through strategic planning and determine the factors that hinder and support the establishment of kampung batik telaga. This type of research uses a qualitative approach with qualitative methods. Data was collected through interviews, observation, literature, and documentation. The results of this study show that women's economic empowerment tactics are compiled on target planning, starting with the socialization of training and supported by the existence of facilities provided and supervised in a sustainable. The strategies use personal and intrapersonal approaches and involve women in all decisions that correlate with Batik villages. From planning a strategy that is right on target, the pattern of empowerment and the emergence of supporting and inhibiting factors that will control the sustainability of the empowerment carried out can be known.